Hopes, tensions and complexity: Indian students' reflections on the relationship of values to management education and future career options - Siememsma, Fran (1999)
This case study was undertaken to explore the way in which postgraduate management students relate their personal values to their current education and future career aspirations. The research primarily focused on the perceptions of students taking an elective offered by the Management Centre for Human Values at the Indian Institute of Management, Calcutta (IIMC). Students' attitudes toward western postgraduate management programme were elicited using interviews and group discussions. Part A of the paper had presented the aiverse range of attitudes analysed under the themes of gender; personal identity; age and status; ethics, religion and spirituality; profit and wealth; as well as consumerism and environmentalism. Part B extends this exploration by direct quotes from students to illustrate their experience of tension and ambiguity, as they anticipated moving from an academic to a business role. - Reproduced
Keywords: Students - India; Management education - India; Management education